Temporal Variations in Concentrations of Ozone, Nitrogen Dioxide, and Carbon Monoxide at Osijek, Croatia - Elvira Kovač-Andrić; Tatjana Radanović; Iva Topalović; Berislav Marković; Nikola Sakač (Advances in Meteorology)
The purpose of this study was to investigate the ozone, carbon monoxide, and nitrogen dioxide variations and their correlation with meteorological parameters in Osijek (Eastern Croatia) during the summer seasons of 2002, 2007, and 2012. The measured data are discussed in relation to the EU guidelines (Directive 2002/3/EC, Directive 2008/50/EC). In order to characterize ambient air with respect to ozone photochemical pollution we calculated three photochemical pollution indicators. These indicators may also be a valid measure for harmful effects on living organisms. The influence of local meteorological parameters on the measured concentrations of ozone, carbon monoxide, and nitrogen dioxide was also investigated. We have attempted to establish correlations between measured pollutant concentrations and meteorological parameters using the technique of multivariate principal component analysis (PCA).